BOOK REVIEW OF RUTH ANN NORDIN’S THE COLD WIFE - Thowaf, Yusron (LANTERN (Journal on English Language, Culture and Literature), 2016)
The Cold Wife story has succeeded to provide interpersonal love stories between the major characters. The Cold Wife story is about a young woman named Carrie Allen who forced to marry with one of her twin brother friend’s, Justin Monroe because her father business goes bankrupt. The conflict arises after Carrie’s confession to her husband that their marriage is a mistake. Fortunately, her husband does not give up and keep trying to allure her heart by struggling to prove his love.